Analisis Ruang Terbuka Hijau Publik Terdampak Banjir di Kota Balikpapan - syafitri, elin diyah; Lady, Gama; Dewanti, Ajeng Nugrahaning; Tufail, Dwiana Novianti (SPECTA Journal of Technology, 2023)
Currently, there is a significant decrease in both the quantity and quality of Green Open Space (RTH), which impacts reducing the quality of the urban environment. The destruction of the buffer zone in the form of green open space has reduced water absorption into the ground, thus impacting the occurrence of floods. This study aims to identify the infiltration capability of green open space affected by floods in Balikpapan City. The main variables used in this study are the distribution of green open spaces and the distribution of flood locations; the analytical method used in this study is the overlay. Based on the research results, results can see that the flood-affected Public Green Open Space has an area of 477.1506 hectares. The number of Public Green Open Spaces affected by flooding is 65 units, with the type of Public Open Space covering urban forests, median road bodies, cemeteries, tourism/sports green open spaces, river borders, and city parks.